Antibodies and antibody‐drug conjugates in the treatment of Hodgkin lymphoma. (9th May 2014) - Eichenauer, Dennis A.; Engert, Andreas
Abstract Hodgkin lymphoma (HL) is a B cell‐derived lymphoid malignancy most often affecting young adults. More than 80% of HL patients achieve long‐term remission after appropriate first‐line treatment consisting of multiagent chemotherapy and/or radiotherapy (RT). In addition, approximately 50% of patients with disease recurrence remain relapse‐free after salvage therapy with high‐dose chemotherapy followed by autologous stem cell transplantation (ASCT). However, patients with multiple relapses are mostly in a palliative situation, and novel drugs for this patient group are needed. Furthermore, novel less toxic but equally effective first‐line and second‐line approaches are required as therapy‐related late sequelae represent a relevant cause of morbidity and mortality in HL survivors. Several antibodies and antibody‐drug conjugates (ADC) targeting CD30 and CD20 have recently been evaluated in HL. Excellent response rates in heavily pretreated patients were observed with the ADC brentuximab vedotin directed against CD30. Thus, ongoing trials investigate brentuximab vedotin in different additional indications. One example is the first‐line treatment of advanced HL where the drug is currently being evaluated in combination with variants of the first‐line protocols ABVD (adriamycin, bleomycin, vinblastine, dacarbazine) and escalated BEACOPP (bleomycin, etoposide, adriamycin, cyclophosphamide, vincristine, procarbazine, prednisone). Anti‐CD20 antibodies given either as single agent or in combination with conventional chemotherapy have also been investigated and still undergo investigation in prospective studies including HL patients. This article reviews the available data on treatment approaches including antibodies and ADC in HL patients.